Short-term Sulpiride Treatment of Children and Adolescents With Tourette Syndrome or Chronic Tic Disorder - Che-Sheng Ho; Hui-Ju Chen; Nan-Chang Chiu; Ein-Yiao Shen; Hung-Chi Lue (Journal of the Formosan Medical Association, 2009)
Tourette syndrome (TS) is characterized by motor and vocal tics, and its diagnosis is based on clinical criteria. Dopamine-blocking neuroleptics are regarded as the most effective drugs for the treatment of TS. Sulpiride is a selective dopamine D2 antagonist. However, only one study with a large number of patients has reported the effect of treatment of TS with sulpiride. The purpose of this study was to evaluate prospectively the effect of sulpiride treatment of children and adolescents with TS or chronic tic disorder. Methods: The inclusion criteria were patients who fulfilled the diagnosis of TS or chronic tic disorder, and who had not received previous treatment. The severity of TS was assessed by the Yale Global Tic Severity Score (YGTSS) every 2 weeks for a total of 6 weeks. The patients started treatment with low-dose sulpiride according to their age on the first visit. The adverse effects of sulpiride were evaluated by subjective complaints from the patients themselves or their parents. The change in scores between each assessment point was analyzed by repeated measures one-way analysis of variance, with SPSS version 12.0 software. Results: One hundred and eighty-nine patients were enrolled. Their average age was 8.0 ± 2.5 years (range, 3–15 years). Most patients were male (n = 165, 87.3%). Six weeks' treatment significantly improved motor tics (p < 0.05), vocal tics (p < 0.05) and total YGTSS (p < 0.05). The most commonly encountered adverse effect was sedation (n = 31, 16.4%). Conclusion: Sulpiride is effective for short-term treatment of children and adolescents with TS or chronic tic disorder, and has few adverse effects.